Transformation of Elderly Spirituality through Suluk: A Phenomenological Study of the Naqshbandi Order in Koto Cayo Village, Semurup - Junita, Nana Nurma; Yusuf, Muhamad; Putra, Pristian Hadi (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2023)
This study aims to provide an in-depth analysis of the worship practices and moral improvement of elderly suluk participants in the Naqshbandi Order at Koto Cayo Village, Semurup, and to identify the factors that support or hinder their participation. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that suluk significantly contributes to enhancing elderly participants’ worship quality, as evidenced by their consistency in performing obligatory and voluntary prayers, increased frequency of fasting, and the habitual practice of daily dhikr. Moreover, suluk plays an important role in moral refinement, eliminating reprehensible traits (akhlaq mazmumah) such as miserliness, arrogance, envy, and jealousy, while fostering praiseworthy virtues (akhlaq mahmudah) such as patience, honesty, humility, generosity, and trust in God (tawakkal). Supporting factors include high intrinsic motivation, family support, financial readiness, and effective time management, whereas inhibiting factors comprise low motivation, limited community support, financial constraints, and work obligations. These findings affirm suluk’s dual role as a medium for spiritual and moral development and as a means of strengthening social solidarity within the community. The study recommends implementing religious motivation programs, disseminating the benefits of suluk, providing economic support, and adjusting schedules to improve elderly participation. The implications of this research are not only relevant for elderly guidance in local contexts but can also serve as a model for developing Islamic values-based spiritual programs across various Muslim communities.